Community Empowerment in Disaster Mitigation Through Dissemination of Research Results in Salua Village, Kulawi District, Sigi Regency - Yulianti Bakari; Hendra Hendra; Muh. Zainuddin Badollahi; Mohamad Fadil; Hilda Anjarsari; Siti Hajar N Aepu (Journal of Universal Community Empowerment Provision, 2026)
A dissemination program for research findings on settlement history, local knowledge, and disaster dynamics in Salua Village, Kulawi District, Sigi Regency, was implemented to strengthen community capacity in disaster mitigation efforts. This activity involved the village government, the Village Consultative Body (BPD), community leaders, women's leaders, and the Disaster Preparedness Group (KSB). Through dissemination and focused discussions (FGDs), findings emerged that village vulnerability is not only caused by ecological factors, but also by the weak role of formal institutions such as the Regional Disaster Management Agency (BPBD) and the forestry service in addressing forest destruction in upstream areas. Furthermore, the unclear function of the KSB also hampers the effectiveness of mitigation at the village level. Local community knowledge including migration history, settlement patterns, language, and experiences with floods and landslides serves as a crucial source of information in formulating community-based mitigation strategies. This program has yielded several outcomes, including increased risk awareness, the creation of participatory risk mapping, identification of the roles of local actors, and recommendations for strengthening village institutions through strengthening the Village-Based Village Council (KSB), implementing customary sanctions, and integrating local knowledge into village disaster documents.